Component Analysis of Capital Structure, Sales Growth and Profitability in Manufacturing Companies Listed on The Indonesia Stock Exchange 2019 and 2020 - Nita Setyawati; Heppy Purbasari (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The implementation of policies caused by the Covid-19 pandemic also affects the performance of manufacturing companies, this is due to the decline in economic activity in the community and social activities by closing public facilities. The purpose of this study was to analyze the differences in the components of capital structure, sales growth and profitability of manufacturing companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. This research is quantitative research with survey method. The data used is secondary data, in the form of data taken from audited financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019 and 2020. Data collection uses documentation techniques with pooled data type. The data needed is in the form of short-term debt (current debt), long-term debt, total debt, equity, sales and net income after interest and taxes. Data analysis includes descriptive statistical test, normality test using the Kolmogorov-Smirnov method, homogeneity test using the Anova Levene Statistic method and hypothesis testing using the Wilcoxon test. The results showed that there were no significant differences in the components of the capital structure including Short Debt to Equity Ratio (SDE), Long-term Debt to Equity Ratio (LDE) and Total Debt to Equity Ratio (TDE). Meanwhile, sales growth and profitability have significant differences from before Covid-19 and after Covid-19.